Feeling Environmental Policing: Possibilities and Challenges for Socio-Ecological Justice. - Schaffer, Kristen; El Halwany, Sarah (Journal of the Canadian Association for Curriculum Studies, 2020)
This is a conceptual paper that merges collaborative acts of storying with theoretical contributions from the affective turn (Clough, 2008) to illustrate ways by which mainstream forms of environmentalism (Klein, 2015) may inscribe normative ways of feeling and being with environments while policing others. Methodologically, we draw on our personal and collective storying-while-walking (Springgay & Truman, 2019) in and around the University of British Columbia (UBC) during the Canadian Society for the Study of Education 2019 conference. We consider how our encounters with/in nature are often disciplined by popular environmentalist discourses (e.g., recycling, greening, contaminating). In our walks/storying, we centre material agents (e.g., trash receptacles, kombucha bottle, tree) as part of affective economies (Ahmed, 2013) that align us to particular ways of feeling (with) nature, for example, embarrassment from not knowing how to recycle a kombucha bottle. We attune ourselves to this hegemonic environmental imaginary, in which certain humans assume control and dominion over nature and reinforce that control via green economies. This compels us to ask: in what ways do environmental efforts for cultivating more response-ability towards nature (Wallace, Higgins & Bazzul, 2018) come to exceed our response-ability with each other as part of nature? How might we follow affective economies that discipline how we value, manage and save nature, and how might this open up pedagogical possibilities for relating differently with each other/nature? With science and environmental education and research in mind, we suggest staying with emotions that make visible acts of environmental policing for socio-ecological justice.